2019
DOI: 10.1007/s00455-019-10010-3
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Factors Related to Food Intake Ability and Swallowing Difficulty After Surgery for Thoracic Esophageal Cancer

Abstract: Swallowing difficulty is among the major complications that can occur after surgery for thoracic esophageal cancer. Recurrent laryngeal nerve paralysis (RLNP) has been considered the most significant cause of a postoperative swallowing difficulty, but association between the two has not been adequately explained. We investigated the relation between postoperative RLNP and swallowing difficulty by means of video fluoroscopy. Our study included 32 patients who underwent subtotal esophagectomy for thoracic esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…Dysphagia, oral intake status, and nutritional status during the perioperative period and six months after surgery This study showed that 34.3% of patients were judged to be unable to start oral intake at one week after esophagectomy, which is consistent with a previous study [33]. These patients were signi cantly more likely to receive tube feeding at discharge, suggesting a good indication for prioritized nutrition education.…”
Section: Prevalence Of Sarcopenia Six Months After Esophagectomysupporting
confidence: 88%
“…Dysphagia, oral intake status, and nutritional status during the perioperative period and six months after surgery This study showed that 34.3% of patients were judged to be unable to start oral intake at one week after esophagectomy, which is consistent with a previous study [33]. These patients were signi cantly more likely to receive tube feeding at discharge, suggesting a good indication for prioritized nutrition education.…”
Section: Prevalence Of Sarcopenia Six Months After Esophagectomysupporting
confidence: 88%
“…Higher cut-offs of SMI are shown to signi cantly increase the prevalence of sarcopenia [30], which might have affected the results of the present study. Dysphagia, intake status, and nutritional status during the perioperative period and six months after surgery This study showed that 34.3% of patients were judged to be unable to start oral intake at one week after esophagectomy, which is consistent with a previous study [33]. These patients were signi cantly more likely to receive tube feeding at discharge, suggesting a good indication for prioritized nutrition education.…”
Section: Prevalence Of Sarcopenia Six Months After Esophagectomysupporting
confidence: 87%
“…RLN paralysis has been believed to be a major cause of dysphagia after esophageal cancer surgery and closely related to the condition 1) . However, in recent years, reports have indicated that RLN paralysis is not directly related to dysphagia and have instead stated that decreased postoperative laryngeal elevation and the inclusion of cervical LND are major risk factors for development of dysphagia [2][3][4] . Yasuda et al 3) indicated that cervical LND may lead to restricted laryngeal elevation due to scarring of the muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased laryngeal elevation may occur as a consequence of restricted elevation of the larynx caused by scarring of the anterior neck mus-cles from cervical lymph node dissection (LND) performed during esophageal cancer surgery 3) . In 2014, Mafune, et al showed that the effects of cervical LND, rather than RLN paralysis, cause dysphagia after this type of surgery 4) .…”
Section: Introductionmentioning
confidence: 99%